THE INFLUENCE OF JOB CRAFTING ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF MEANINGFUL WORK AMONG HOSPITAL EMPLOYEES - Indri Lestari; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the influence of Job Crafting on Organizational Citizenship Behavior (OCB) through the mediating role of Meaningful Work among hospital employees. In the healthcare sector, employees are required not only to perform their formal responsibilities but also demonstrate voluntary behaviors that support teamwork, organizational effectiveness, and service quality. Job Crafting represents employees’ proactive efforts to modify and optimize their work experiences, while Meaningful Work reflects employees’ perceptions of purpose, significance, and value in their jobs. This study applies a quantitative approach using a cross-sectional survey design involving hospital employees. Data were collected through questionnaires measuring Job Crafting, Meaningful Work, and Organizational Citizenship Behavior using a Likert scale. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and mediation analysis. The results indicate that Job Crafting has a positive and significant effect on Organizational Citizenship Behavior. Meaningful Work also has a positive and significant effect on Organizational Citizenship Behavior, demonstrating that employees who perceive greater meaning in their work are more likely to engage in voluntary behaviors that support the organization. Furthermore, the regression model shows that Job Crafting and Meaningful Work simultaneously contribute significantly to explaining variations in Organizational Citizenship Behavior among hospital employees.